Delivering Bad News: Analysis of Leadership Communication Strategies and Channel Selection - Henry, Levor (Digital Repository of Theses - SSBM Geneva, 2025)
This study was conducted to understand how leaders deliver bad news in organizational contexts, focusing on the ways in which the nature and severity of the information shape communication choices and influence employee perceptions. Delivering bad news is a frequent yet highly sensitive aspect of leadership, and ineffective handling of such conversations can undermine trust, morale, and organizational credibility. Conversely, skillful delivery can preserve relationships and reinforce employee engagement during times of difficulty. Recognizing this dual potential, the study examined leadership communication practices to identify patterns, strategies, and best practices that can guide more effective organizational responses. A sequential mixed-methods design was employed to capture both generalizable trends and nuanced insights. Quantitative data were collected through surveys completed by 101 leaders across a variety of business sectors, while qualitative perspectives were obtained through open-ended responses and follow-up interviews with a purposively selected subset of participants. The study was guided by five core objectives: to describe the types of information leaders most often classify as bad news; to examine their preferred communication channels and the rationales behind those choices; to analyze how message severity influences channel selection; to evaluate which communication strategies are associated with positive employee perceptions; and to identify evidence-based best practices that support effective leadership communication. Findings revealed that performance-related issues, such as failed evaluations or assignment rework, were the most frequently reported forms of bad news, while more severe matters, layoffs, suspensions, and demotions, though less common, carried far greater emotional weight for both leaders and employees. Face-to-face communication emerged as the most trusted channel in high-severity situations, with video conferencing serving as a viable substitute in remote or hybrid contexts. Email and telephone were more commonly used for low-severity or routine matters. While many leaders justified their channel selection on the grounds of appropriateness and organizational fit, a notable number admitted that convenience or habit influenced their choices, underscoring a gap between ideal communication practices and real-world behavior. The study also confirmed the importance of empathetic and transparent leadership strategies in shaping positive employee perceptions. Leaders who demonstrated emotional intelligence, sensitivity to employee concerns, and clarity in their delivery reported more constructive responses from their teams. Practices such as combining verbal communication with follow-up written documentation, maintaining openness to employee questions, and engaging in reflective learning after difficult conversations were identified as effective approaches for sustaining trust and improving communication competence. The results suggest that aligning communication channels with message severity, integrating empathy and respect into leadership practices, and embedding reflective learning into organizational routines can significantly improve outcomes when bad news must be delivered. This research contributes to leadership and communication scholarship by integrating Media Richness Theory, Situational Crisis Communication. Theory, Emotional Intelligence, and Transformational Leadership into a multi-theoretical framework. It also offers practical guidance for organizations seeking to strengthen leadership development, enhance trust, and foster resilience during periods of organizational difficulty.